Seleção e operação ótima de tecnologia para o aproveitamento de biogás na geração de energia elétrica - Binotto, Jessica Marques (2017)
The use of organic waste to generate electricity in a distributed way is an alternative that needs to be carefully evaluated due to the various advantages related to this process. Specifically, intensive livestock farming is an activity that results in high generation of waste with high pollutant power, whose treatment is mandatory by law and, if carried out through the controlled anaerobic process, generates biogas. Due to its high calorific value, biogas can be used as a primary source for the generation of electric energy, which requires the joint evaluation of environmental, social, political and economic benefits. The Integrated Resource Planning (IRP) appears as an adequate tool to carry out such an evaluation, considering all the bonuses and onuses involved. In this sense, this work analyzes the use of biogas as a primary source for generation of electric power in a rural property located in the western region of the state of Paraná, under the IRP perspective. For the economic evaluation, a mathematical model was developed, considering the VaR (Value at Risk) as a measure of the risk to which the investor is subject due to the uncertainty of the demand and the production of biogas. The simulations were performed using a hypothetical rural property considering a VaR with a confidence level of 95%. The developed model, together with the evaluation criteria proposed by the IRP, was an adequate tool to point out the benefits of using biogas as an energy resource.